Flânerie as a strategy - Duka, Sanita (Amfiteater (Ljubljana), 2025)
The article discusses the essay “Naples” (1925), co-authored by Asja Lacis (née Anna Liepina, married Lacis or Lace, 1891–1979) and Walter Benjamin (1892–1940). This case study reflects flânerie used as a creative strategy. The narrator, a figure of urban wandering and detached observation, was implemented by the co-authors stressing the differences in the interpretation by a man and a woman – flâneur and flâneuse. They portray Naples through contrasting perspectives: Benjamin, the philosopher, views the city as a system, examining its structures and categories, while Lacis, the theatre director, approaches it as a dynamic performance. This convergence of viewpoints creates a unique narrative voice. The article sheds light on the theatrical implications used in urban exploration and proves the input of Lacis by exploring parallels in her educational experience, creative works, letters and publications. Under the influence of collaboration with Lacis, Benjamin developed the signature philosophical style and initial impulse in this essay by introducing metaphors of porosity and constellation, later developed as concepts. The paper concludes that flânerie, used as a strategy of exploration and narration, integrates the vitality of lived experience with theatre and philosophy to inspire fresh perspectives on seeing and being in the world, thus embodying the revolutionary avant-garde pursuit of transcending boundaries, whether artistic, ideological or cultural and reinforcing its innovative and transformative intent.
Keywords: constellation; creative colloboration; flaner in flanerka; flâneur and flâneuse; gledališkost urbanega okolja; konstelacija; lived experience; Naples; narrative voice; Neapelj; porosity; poroznost; pripovedni glas; urban theatricality; ustvarjalno sodelovanje; živa izkušnja